Efek Serbuk Jahe Merah (Zingiber Officinale Var Rubrum) Terhadap Penurunan Intensitas Dismenore Pada Siswi SMAN 1 Muncang Kabupaten Lebak Banten : The Effect of Red Ginger Powder (Zingiber Officinale Var Rubrum) on Reducing the Intensity of Dysmenorrhea in Female Students of SMAN 1 Muncang, Lebak Regency, Banten - Awalia, Lieska (Dohara POAJ, 2023)
Introduction: Dysmenorrhea is a condition that occurs during menstruation or menstruation which can interfere with activities and requires treatment which is characterized by pain or pain in the abdominal or pelvic area